Physico-chemical parameters of the habitat of molluscs, intermediate hosts of schistosomes, in Kisangani and its surroundings - Sapu , KANGANGA John; Abedi Mwana Kimbulu, Médard; TAGOTO , TEPUNGIPAME Alliance; Falay Sadiki, Dadi; Losimba Likwela, Joris; Bobanga Lengu, Thierry (Orapuh Journal, 2025)
Introduction Schistosomiasis, a neglected tropical disease, is caused by Schistosoma trematodes and is prevalent in 78 countries, particularly in sub-Saharan Africa. The distribution of these parasites is linked to the presence of their intermediate hosts, freshwater molluscs. The survival and development of these molluscs are influenced by the physico-chemical conditions of their habitat, including water temperature, pH, conductivity, and oxygen levels. Understanding these relationships is crucial for schistosomiasis control. Purpose This study aimed to determine the correlation between the physico-chemical parameters of mollusc habitats and the number of molluscs collected within 30-minute intervals in Kisangani, DRC, and its surroundings. Methods The research was conducted in five marshy sites in Tshopo Province. Molluscs were collected, and water samples were analysed for temperature, pH, turbidity, conductivity, oxygen saturation, and dissolved oxygen. Mollusc density was assessed by counting the number collected in 30 minutes. Data were analysed using Microsoft Excel and R software, with statistical significance set at 5%. Results Mollusc density varied across the sites, with some sites showing high densities and others moderate. Physico-chemical parameters also varied; however, no statistically significant correlation was found between the number of molluscs collected and these parameters. Conclusion The study found no significant correlation between mollusc counts and the measured physico-chemical parameters. Factors such as human activity, spatial scale, and other unmeasured environmental variables may influence mollusc abundance. Further research is recommended to explore specific factors affecting mollusc populations in the region.